Battery electrodes and batteries
By optimizing the porosity distribution in the battery electrode composite material layer, especially setting high porosity in the second area, the problem of porosity distribution deviation in the prior art is solved, and the good permeability of the electrolyte and the improvement of the high-magnification characteristics of the battery are achieved.
Patent Information
- Application Number
- CN202180019707.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-19
- Filing Date
- 2021-01-14
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-01-14
AI Technical Summary
The porosity distribution of the existing battery electrode composite material layer in the thickness direction is prone to deviation, resulting in poor permeability of the electrolyte and reduced high-magnification characteristics.
By slicing the composite material layer in three equal parts along the thickness direction and setting a high porosity in the second area, it ensures good permeability of the electrolyte, and at the same time, the porosity is controlled in the first and third areas to maintain the stability of the overall structure.
The electrolyte is good permeability to the composite material layer, the high-magnification characteristics of the battery are improved, and the performance degradation caused by pore distribution deviation is avoided.
Smart Images

Figure CN115280540B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a battery electrode and a battery including the electrode. Background Art
[0002] The electrodes of lithium-ion batteries and the like are usually manufactured by applying an electrode composite material slurry containing an active material, a binding material, etc. to the surface of a core material as a metal foil, and drying and compressing the coating film by a wet process (for example, refer to patent document 1). In this case, during the drying process of the coating film, the migration of the binding material from the core material side to the surface side is caused, and the amount of the binding material near the surface increases compared to the vicinity of the core material, and the distribution of the binding material in the thickness direction is prone to deviation. In addition, in the coating film, for example, there are pores between the particles of the active material. When the coating film is compressed, the pores are reduced due to the movement of the particles of the active material, but because the coating film is fixed on the core material, the closer to the core material, the more difficult it is for the composite material to move, and therefore, many pores remain, and the distribution of the pores in the thickness direction is prone to deviation.
[0003] In recent years, a method has been proposed in which an electrode composite material is formed into a sheet after being calendered and then adhered to a core material to manufacture an electrode (for example, see Patent Documents 2 and 3). Patent Document 2 discloses the following method: the pressure applied between a pair of rollers for pressurizing a laminate of a compressed powder layer and a core material is made greater than the pressure applied between a pair of rollers for pressurizing the powder of the electrode composite material to make a compressed powder layer, so that the compressed powder layer adheres to the core material and then undergoes high density. In addition, Patent Document 3 discloses a method in which a granulated material formed by a mixture of an active material, a thickening material, a solvent, and a binding material is formed into a sheet and the sheet is arranged on a core material.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2005-056743
[0007] Patent Document 2: Japanese Patent Application Publication No. 2013-77560
[0008] Patent Document 3: Japanese Patent Application Publication No. 2015-138658 Summary of the invention
[0009] According to the methods disclosed in Patent Documents 2 and 3, the drying process of the composite material layer can be omitted or simplified, and the problems in the above-mentioned wet process can be expected to be improved. However, for the methods of Patent Documents 2 and 3, as with the wet process, deviations are easily produced in the distribution of porosity in the thickness direction of the composite material layer, and there is still a lot of room for improvement. The more pores there are in the region of the core material closer to the composite material layer. In other words, if the distribution of porosity is formed so that the closer to the surface pores of the composite material layer, the less, the permeability of the electrolyte to the composite material layer becomes poor, for example, resulting in a reduction in high-rate characteristics. In addition, according to the specific process conditions of Patent Documents 2 and 3, it is difficult to densify the composite material layer.
[0010] The battery electrode disclosed in the present invention is characterized in that it comprises: a core material; and a composite material layer, which contains an active material and a binding material and is arranged on the surface of the aforementioned core material, and when the aforementioned composite material layer is divided into three equal parts along the thickness direction and defined as the first region, the second region and the third region in sequence from the aforementioned core material side, the porosity of the aforementioned second region is higher than the porosity of the aforementioned first region.
[0011] The battery disclosed herein comprises: the battery electrode described above; and an electrolyte solution.
[0012] According to one embodiment of the present disclosure, a battery electrode including a composite material layer having good electrolyte permeability can be provided. In addition, a battery including the electrode of the present disclosure has, for example, excellent high rate characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 It is a cross-sectional view of a battery as an example of an embodiment.
[0014] Figure 2 It is a cross-sectional view of a positive electrode as an example of an embodiment.
[0015] Figure 3 Graph showing the relationship between the density of the positive electrode composite material layer and the permeability of the non-aqueous electrolyte.
[0016] Figure 4 It is a figure which shows the manufacturing method of the positive electrode as 1st Embodiment.
[0017] Figure 5 It is a diagram showing a method for producing a positive electrode according to the second embodiment.
[0018] Figure 6 It is a figure which shows the manufacturing method of the positive electrode which is 3rd Embodiment.
[0019] Figure 7 It is a figure which shows the manufacturing method of the positive electrode which is 4th Embodiment.
[0020] Figure 8It is a figure which shows the manufacturing method of the positive electrode which is 5th Embodiment. DETAILED DESCRIPTION
[0021] The following is a detailed description of the embodiment of the battery electrode disclosed in the present invention. The embodiment described below is only an example, and the present invention is not limited to the following embodiment. In addition, the drawings referred to in the description of the embodiment are schematically recorded, and the size ratios of the components depicted in the drawings should be judged with reference to the following description.
[0022] The battery electrode disclosed in the present invention is suitable for the electrode of a non-aqueous electrolyte secondary battery such as a lithium ion battery, but can also be used in a battery containing an aqueous electrolyte. In addition, it is not limited to a secondary battery, and can also be used in a primary battery. Hereinafter, a non-aqueous electrolyte secondary battery and an electrode for a non-aqueous electrolyte secondary battery (particularly a positive electrode) are cited as examples for explanation.
[0023] Figure 1 FIG. 2 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1 As shown, the nonaqueous electrolyte secondary battery 10 includes a wound electrode body 14, a nonaqueous electrolyte, and an outer shell can 16 for storing the electrode body 14 and the electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The outer shell can 16 is a metal container in a bottomed cylindrical shape with one side open in the axial direction, and the opening of the outer shell can 16 is blocked by a sealing body 17. In the following, for the sake of convenience of description, the sealing body 17 side of the battery is regarded as the upper side, and the bottom side of the outer shell can 16 is regarded as the lower side.
[0024] It should be noted that the outer shell of the battery is not limited to a cylindrical outer shell can, for example, it can be a square outer shell can, or it can be an outer shell composed of a laminated sheet including a metal layer and a resin layer. In addition, the electrode body can be a stacked electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked with a separator.
[0025] The non-aqueous electrolyte solution comprises a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent may be, for example, esters, ethers, nitriles, amides, and mixed solvents of two or more thereof. The non-aqueous solvent may contain a halogen substitution body formed by replacing at least a portion of the hydrogen of these solvents with a halogen atom such as fluorine. The electrolyte salt may be, for example, a lithium salt such as LiPF6.
[0026] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, and are alternately stacked along the radial direction of the electrode body 14 by being wound into a spiral shape. In order to prevent the precipitation of lithium, the negative electrode 12 is formed to be one circle larger than the positive electrode 11. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in the length direction and the width direction (width direction). The two separators 13 are formed to be at least one circle larger than the positive electrode 11, for example, and are arranged in a manner of clamping the positive electrode 11. The electrode body 14 has: a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0027] Insulating plates 18 and 19 are disposed above and below the electrode body 14 , respectively. Figure 1 In the example shown, the positive electrode lead 20 extends toward the sealing body 17 through the through hole of the insulating plate 18, and the negative electrode lead 21 extends toward the bottom side of the outer can 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the cover 27 electrically connected to the internal terminal plate 23, serves as the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer can 16 by welding or the like, and the outer can 16 serves as the negative terminal.
[0028] A gasket 28 is provided between the outer shell can 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 is formed on the outer shell can 16, with a portion of the side portion protruding inwardly for supporting the sealing body 17. The groove portion 22 is preferably formed in a ring shape along the circumferential direction of the outer shell can 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer shell can 16 through the groove portion 22 and the open end of the outer shell can 16 that is pressed and connected to the sealing body 17.
[0029] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 to the cover 27 side, thereby blocking the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the cover 27.
[0030] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 , particularly the positive electrode 11 , will be described in detail.
[0031] [positive electrode]
[0032] Figure 2 FIG. 1 is a cross-sectional view of a positive electrode 11 as an example of an embodiment. Figure 2 As shown, the positive electrode 11 includes: a positive electrode core material 30, and a positive electrode composite material layer 31 disposed on the surface of the positive electrode core material 30. The positive electrode core material 30 can use a foil of a metal such as aluminum or aluminum alloy that is stable within the potential range of the positive electrode 11, a thin film of the metal disposed on the surface, etc. The positive electrode composite material layer 31 preferably includes a positive electrode active material, a binding material, and a conductive material, and is disposed on both sides of the positive electrode core material 30. As conductive materials, carbon materials such as carbon black, acetylene black, Ketjen black, graphite, and carbon nanotubes can be exemplified. The content of the conductive material is preferably 0.01 to 5% by mass relative to the mass of the positive electrode composite material layer 31. The conductive material can be used alone or composited with an active material in advance.
[0033] The positive electrode composite material layer 31 is formed by bonding the positive electrode composite material sheets 43, 43x, 53 produced by the manufacturing method described later to the surface of the positive electrode core material 30. When the positive electrode composite material layer 31 is composed of the positive electrode composite material sheets 43, 43x, the positive electrode composite material layer 31 contains, for example, a fibrous binder as a binder. By using the fibrous binder, the positive electrode composite material 40 (see the following) is bonded to the positive electrode core material 30. Figure 4 It should be noted that in this specification, the "positive electrode composite material layer 31" can be replaced by "positive electrode composite material sheet 43, 43x, 53".
[0034] The positive electrode composite material layer 31 is composed of a positive electrode active material as a main component (the component with the highest mass ratio). The content of the positive electrode active material is preferably 85 to 99 mass %, more preferably 90 to 98 mass % relative to the mass of the positive electrode composite material layer 31. The volume-based median particle size (D50) of the positive electrode active material is, for example, 1 to 30 μm, preferably 2 to 15 μm. In addition, the thickness of the positive electrode composite material layer 31 is, for example, 30 to 300 μm, preferably 30 to 120 μm, and more preferably 50 to 100 μm.
[0035] The positive electrode active material can use a lithium transition metal composite oxide. As the metal element contained in the lithium transition metal composite oxide, Ni, Co, Mn, Al, B, Mg, Ti, V, Cr, Fe, Cu, Zn, Ga, Sr, Zr, Nb, In, Sn, Ta, W, etc. can be cited. Among them, it is preferred to contain at least one of Ni, Co, and Mn. As an example of a suitable composite oxide, a lithium transition metal composite oxide containing Ni, Co, and Mn and a lithium transition metal composite oxide containing Ni, Co, and Al can be cited.
[0036] The fibrous binder is, for example, made of a resin having polytetrafluoroethylene (PTFE) as the main component, which is obtained by fibrillating PTFE particles. The content of the fibrous binder is preferably 0.05 to 5% by mass relative to the mass of the positive composite material layer 31. In addition, the positive composite material layer 31 may also include a binder that is not fibrillated (not fibrous). As an example of a binder that is not fibrillated, polyvinylidene fluoride (PVdF) can be cited.
[0037] There are pores in the positive electrode composite material layer 31. The pores formed inside the positive electrode composite material layer 31 are connected to the surface of the positive electrode composite material layer 31, for example. Moreover, such pores become channels for the electrolyte, improving the permeability of the electrolyte to the positive electrode composite material layer 31. In the positive electrode 11, when the positive electrode composite material layer 31 is divided into three equal parts in the thickness direction and defined as the first region 31a, the second region 31b and the third region 31c in sequence from the positive electrode core material 30 side, the porosity (b) of the second region 31b becomes higher than the porosity (a) of the first region 31a. Here, porosity refers to the ratio of pores in the positive electrode composite material layer 31.
[0038] That is, in the positive electrode composite material layer 31, there are more pores in the central part of the layer thickness direction compared with the vicinity of the positive electrode core material 30. If the positive electrode is manufactured by the general wet process in the past, the pores near the positive electrode core material of the positive electrode composite material layer become more, and the more away from the core material, the fewer pores, but according to the manufacturing method described later, pores can be formed in the second region 31b compared with the first region 31a. In this case, the permeability of the electrolyte to the positive electrode composite material layer 31 is improved, and the high rate characteristics of the battery are improved.
[0039] The porosity of the positive electrode composite material layer was measured by the following method.
[0040] (1) Using an ion milling device (for example, IM4000PLUS manufactured by Hitachi High-Tech Corporation), a cross section of the positive electrode composite material layer is exposed.
[0041] (2) Using a scanning electron microscope (SEM), a reflected electron image of the cross section of the exposed positive electrode mixture layer is taken. The magnification of the reflected electron image is 1000 to 5000 times.
[0042] (3) The SEM image of the cross section of the positive electrode composite material layer is recorded in a computer and divided into three colors based on contrast using image analysis software (eg ImageJ manufactured by the National Institutes of Health, USA), with the intermediate colors being regarded as pores.
[0043] (4) A measurement target region is selected from the processed image, the total area of pores in the region is obtained, and the ratio of pores to the measurement target region (porosity) is calculated.
[0044] As described above, the porosity of the positive electrode composite material layer 31 is higher in the second region 31b than in the first region 31a. For example, the difference (ba) between the porosity (b) of the second region 31b and the porosity (a) of the first region 31a is 0.5% or more. On the other hand, it is preferred that the porosity difference (ba) is not excessively large, preferably 10% or less, more preferably 5% or less.
[0045] The porosity (b) of the second region 31b may be higher than the porosity (c) of the third region 31c. For example, the difference (bc) between the porosity (b) and the porosity (c) is 0.5% or more. The porosity difference (bc) is preferably not too large, preferably 10% or less, and more preferably 5% or less.
[0046] In addition, the difference (ac) between the porosity (a) of the first region 31a and the porosity (c) of the third region 31c is, for example, within the range of ±1%. The porosity (a) and the porosity (c) may be substantially the same. An example of a suitable positive electrode composite material layer 31 is porosity (a) ≒ porosity (c) < porosity (b), and the pores are present in the entire layer without omission rather than unevenly in a part of the positive electrode composite material layer 31. In this case, the electrolyte becomes easy to penetrate into the entire positive electrode composite material layer 31.
[0047] The porosity (c) of the third region 31c may be higher than the porosity (b) of the second region 31b, and the porosity of the positive electrode composite material layer 31 may be porosity (a) < porosity (b) < porosity (c). In this case, good permeability of the electrolyte can also be obtained. For example, the difference (cb) between the porosity (c) and the porosity (b) is 0.5% or more. In addition, the porosity difference (cb) is preferably 10% or less, more preferably 5% or less.
[0048] From the viewpoint of increasing capacity, the overall porosity of the positive electrode composite material layer 31 is preferably 40% or less, more preferably 30% or less. On the other hand, from the viewpoint of improving the permeability of the electrolyte, the overall porosity of the positive electrode composite material layer 31 is preferably 5% or more, more preferably 10% or more.
[0049] In the positive electrode composite material layer 31, the content of the binding material is preferably roughly uniform in the entire layer, or becomes higher on the positive electrode core material 30 side. In this case, the bonding force of the positive electrode composite material layer 31 to the positive electrode core material 30 is improved, and the permeability of the electrolyte is further improved. It should be noted that if the positive electrode is manufactured by a general wet process in the past, the migration of the binding material will be caused during the drying process of the coating, and the amount of the binding material near the surface will increase compared to the vicinity of the core material.
[0050] In one example of a suitable positive electrode composite material layer 31, the ratio ((ac)×100 / (a+b+c)) of the difference between the content (a) of the binder in the first region 31a and the content (c) of the binder in the third region 31c relative to the content (a+b+c) is within the range of ±5%. The content (a) and the content (c) may be substantially the same.
[0051] In addition, the ratio of the difference (ab) between the content (a) and the content (b) of the binder in the second region 31b to the content (a+b+c) ((ab)×100 / (a+b+c)) is within the range of ±5%. Similarly, the ratio of the difference between the content (b) and the content (c) to the content (a+b+c) ((bc)×100 / (a+b+c)) is within the range of ±5%. That is, an example of a suitable positive electrode composite material layer 31 is a positive electrode composite material layer having a content (a) of Content (b) The content (c) is such that the binder is present throughout the entire layer without omission, rather than being unevenly present in a part of the positive electrode composite material layer 31 .
[0052] In another example of a suitable positive electrode composite material layer 31, the content of the binder increases in the order of the third region 31c, the second region 31b, and the first region 31a (content (c) < content (b) < content (a)). However, it is preferred that the difference in content in each region is not too large, and the above ratios ((ac)×100 / (a+b+c)) and ((bc)×100 / (a+b+c)) are preferably 20% or less, more preferably 10% or less, respectively.
[0053] The density of the positive electrode composite material layer 31 is not particularly limited, and the effect of the present disclosure becomes more significant when the density is high. The density of the positive electrode composite material layer 31 is, for example, 3.5 g / cc or more, preferably 3.6 g / cc or more, and more preferably 3.8 g / cc or more. The upper limit of the density of the positive electrode composite material layer 31 is, for example, 4.3 g / cc.
[0054] Figure 3Graph showing the relationship between the density of the positive electrode composite material layer 31 (embodiment) and the permeability of the non-aqueous electrolyte. As a comparison, the permeability of the positive electrode manufactured by the general wet process in the past is shown. In this experiment, multiple samples with different densities of the composite material layer were made, propylene carbonate (PC) was used instead of the non-aqueous electrolyte, a specified amount of PC was dripped on each composite material layer, and the time from the PC immersion to its disappearance was measured. The shorter the time, the better the permeability of the electrolyte. It should be noted that the porosity and the content of the binding material of the positive electrode composite material layer of the embodiment / comparative example used in this experiment are shown in Table 1 (the same positive active material is used and the same addition amount is set).
[0055] [Table 1]
[0056] Positive electrode composite material layer of the embodiment Positive electrode composite material layer of comparative example Porosity of the first region 25.9% 31.5% Porosity of the second region 26.8% 28.6% Porosity of the third region 25.1% 29.5% Content ratio of the adhesive material in the first region 33% 17% Content ratio of adhesive material in the second region 33% 31% Content of adhesive material in the third region 34% 52%
[0057] Depend on Figure 3 It can be seen that the positive electrode composite material layer of the embodiment has a short liquid disappearance time and good electrolyte permeability compared with the positive electrode composite material layer of the comparative example. In addition, in the positive electrode composite material layer of the comparative example, the permeability of the electrolyte decreases sharply when the density becomes high, but according to the positive electrode composite material layer of the embodiment, the decrease in permeability is suppressed, and even at high density, it has good permeability.
[0058] In the positive electrode 11, the positive electrode active material can be impregnated into the positive electrode core material 30. The maximum impregnation depth D of the positive electrode active material is, for example, more than 30% of the thickness of the positive electrode core material 30, and as a specific example, it is more than 6 μm. Here, the impregnation depth D of the positive electrode active material refers to the length of the positive electrode core material 30 along the thickness direction from the surface of the positive electrode core material 30 to the most impregnated part of the positive electrode active material. The immersion depth D can be measured by observing the cross-section of the positive electrode 11 using an SEM. It should be noted that the maximum immersion depth D can be controlled, for example, according to the softening temperature of the positive electrode core material 30, the heating temperature in the hot pressing process described later, and the pressing pressure.
[0059] [negative electrode]
[0060] The negative electrode 12 comprises: a negative electrode core material composed of metal foil or the like, and a negative electrode composite material layer provided on the surface of the negative electrode core material. The core material of the negative electrode can generally use copper foil. The negative electrode 12 can use a conventionally known electrode plate manufactured by a wet process, or can use an electrode plate having a negative electrode composite material sheet manufactured by a method described later. The negative electrode 12 comprises a negative electrode composite material layer in which the porosity of the second region is higher than the porosity of the first region, and can have the same structure as the positive electrode 11 described above.
[0061] The negative electrode active material can use carbon-based active materials such as natural graphite such as flaky graphite, block graphite, and earthy graphite, block artificial graphite (MAG), and artificial graphite such as graphitized mesophase carbon microbeads (MCMB). In addition, the negative electrode active material can also use Si-based active materials alloyed with lithium. It should be noted that the carbon-based active material has high electronic conductivity compared to the positive electrode active material, so the negative electrode 12 may not contain a conductive material.
[0062] [Separator]
[0063] The separator 13 may be a porous sheet having ion permeability and insulation. Specific examples of the porous sheet include microporous films, woven fabrics, nonwoven fabrics, etc. Suitable materials for the separator 13 include polyolefins such as polyethylene and polypropylene, cellulose, etc. The separator 13 may be a single-layer structure or a laminated structure. A heat-resistant layer may be formed on the surface of the separator 13.
[0064] [Manufacturing method of positive electrode]
[0065] The following is a detailed description of the method for manufacturing the positive electrode 11. The following is an example of a method for manufacturing the positive electrode 11 including a conductive material, but the following manufacturing method can also be used in the same manner for manufacturing the negative electrode. In the case of the negative electrode, a negative electrode active material is used instead of a positive electrode active material, and a conductive material may not be added to the composite material sheet.
[0066] Figure 4 1 is a diagram showing an example of a method for manufacturing the positive electrode 11. Figure 4 As shown, in the manufacturing process of the positive electrode 11, the powdered positive electrode composite material 40 is rolled and formed into a sheet to make a positive electrode composite material sheet 43, and the positive electrode composite material sheet 43 is attached to the positive electrode core material 30 to manufacture the positive electrode 11. In this process, before the positive electrode composite material sheet 43 is attached to the positive electrode core material 30, the sheet is strongly compressed to achieve high density. Thus, a positive electrode composite material sheet 43 (positive electrode composite material layer 31) having the above-mentioned pore distribution is obtained.
[0067] Figure 4 The example shown is a dry process. The dry process is a process in which the active material and the binding material are mixed without using a solvent, and the active material and the binding material are mixed at a solid content concentration of substantially 100%. Conductive materials other than the active material and the binding material can be added during mixing, and even when materials other than the active material and the binding material are added, the solid content concentration during mixing is substantially 100%.
[0068] For the positive electrode composite material 40, for example, a positive electrode active material, a binding material particle and a conductive material can be put into a mixer, and the binding material particles are fibrillated while mixing these materials to obtain. The positive electrode composite material 40 includes a granular active material and a fibrous binding material, and the fibrous binding material is attached to the particle surface of the active material and intertwined with the active material. In other words, the active material is maintained by the fibrous binding material that exists in a mesh shape. This form can also be confirmed in the extreme composite material sheet 43.
[0069] The binder particles are preferably particles with polytetrafluoroethylene (PTFE) as the main component. PTFE is easily fibrillated and is suitable as a binder for the positive electrode composite material sheet 43. For example, PTFE particles with a volume-based median particle size (D50) of 5 to 100 μm are used and mixed with the active material and the conductive material in a short time. In this case, a positive electrode composite material 40 in which the particle rupture of the active material is suppressed and the amount of conductive material incorporated into the fibrous binder material is small can be produced. The mixer can use a milling cutter, a pin mill, a bead mill, a microparticle composite device, a granulator, a mixer, etc.
[0070] like Figure 4 As shown in (a) to (c), the positive electrode composite material sheet 43 is produced through multiple calendering and compression steps. First, the positive electrode composite material 40 is calendered into a sheet using a pair of rollers 100. The two rollers 100 are arranged at a predetermined interval (for example, 1 to 3 mm) and rotate in the same direction (for example, a peripheral speed of 0.5 to 1.5 m / min). The positive electrode composite material 40 is supplied to the gap between the two rollers 100 and calendered to form a positive electrode composite material sheet 41. Second, the positive electrode composite material sheet 41 is further calendered to obtain a positive electrode composite material sheet 42 that is thinner than the positive electrode composite material sheet 41 and has a high density. Third, the positive electrode composite material sheet 42 is further compressed to obtain a positive electrode composite material sheet 43 that is thinner than the positive electrode composite material sheet 42 and has a high density.
[0071] The positive electrode composite material sheet 41 is rolled using three rolls 101 a , 101 b , and 101 c . Figure 4 In the example shown, the three rollers are arranged in a row at a predetermined interval (e.g., 50 to 200 μm), and the rollers 101a and 101b rotate in the same direction, and the roller 101c rotates in the opposite direction to the two. The positive electrode composite material sheet 41 is rolled between the rollers 101a and 101b and between the rollers 101b and 101c to form a positive electrode composite material sheet 42. The peripheral speed ratio of the three rollers can be different. For example, the peripheral speed of the roller 101b can be 1.5 to 3 times the peripheral speed of the roller 101a, and the peripheral speed of the roller 101c can be 1.2 to 2 times the peripheral speed of the roller 101b.
[0072] The positive electrode composite material sheet 42 is compressed using a pair of rollers 102 (for example, the spacing is set to 0 μm). The positive electrode composite material sheet 42 is compressed with a force greater than that in the first and second calendering steps, and is formed into a positive electrode composite material sheet 43 that constitutes the positive electrode composite material layer 31. The thickness, density, and pore distribution of the positive electrode composite material sheet 43 are determined by the compression step, and are substantially unchanged in the step after joining with the positive electrode core material 30. The press line pressure using the roller 102 is, for example, more than 10 times the press line pressure in the first and second calendering steps, preferably 15 to 25 times, and as a specific example, is 1.0 to 3 t / cm. In addition, the positive electrode composite material sheet 42 can be compressed while being heated at a temperature of 50 to 200°C.
[0073] like Figure 4 As shown in (d) , by attaching the positive electrode composite material sheet 43 to the positive electrode core member 30 , the positive electrode 11 is obtained in which the positive electrode composite material layer 31 formed of the positive electrode composite material sheet 43 is provided on the surface of the positive electrode core member 30 . Figure 4 In the example shown, a pair of rollers 103 are used to hot-press the stack of the positive electrode core material 30 and the positive electrode composite material sheet 43, so that the positive electrode composite material sheet 43 is bonded to the surface of the positive electrode core material 30. The press line pressure by the roller 103 is preferably less than the press line pressure by the roller 102. In addition, the positive electrode composite material sheet 43 is preferably heated at a temperature below the melting point of the binding material, and can also be heated at a temperature above the softening temperature of the positive electrode core material 30 and below the melting point of the fibrous binding material. The hot pressing temperature is set, for example, to 150 to 250°C.
[0074] The positive electrode composite material sheets 43 are joined to both surfaces of the positive electrode core material 30 . Figure 4 In the example shown, after one positive electrode composite material sheet 43 is bonded to one surface of the positive electrode core material 30, another positive electrode composite material sheet 43 is bonded to the other surface. Figure 5 As shown, two positive electrode composite material sheets 43 may be bonded to both surfaces of the positive electrode core material 30 at the same time. Figure 5 In the example shown, the positive electrode core material 30 and two positive electrode composite material sheets 43 are supplied between a pair of rollers 103 , and the two positive electrode composite material sheets 43 are simultaneously hot-pressed.
[0075] In the positive electrode composite material layer 31 of the positive electrode 11 manufactured by the above process, a pore distribution is formed in which the porosity (a) of the first region 31a ≒ the porosity (c) of the third region 31c < the porosity (b) of the second region 31b. The difference between the porosity (b) and the porosity (a, c) is not large, and the pores are present in the entire positive electrode composite material layer 31 without omission, and the permeability of the electrolyte is good. This pore distribution is obtained by compressing the positive electrode composite material sheet 42 in a state that is not constrained by the positive electrode core material 30, etc. In addition, in this process, no solvent is used in the preparation of the positive electrode composite material sheet 43, and therefore, the migration of the binding material is not caused, and the binding material is roughly uniformly present in the entire positive electrode composite material layer 31.
[0076] Figure 6 and Figure 7 1 is a diagram showing another example of a method for manufacturing the positive electrode 11. Figure 6 and Figure 7 As shown, the positive electrode 11 can be manufactured using a positive electrode composite material sheet 53 produced by a wet process.
[0077] like Figure 6 As shown in (a) to (c) of FIG. 5 , the positive electrode composite material sheet 53 can be manufactured as follows: a positive electrode composite material slurry 50 containing a positive electrode active material, a binder, a conductive material and a solvent is applied on a release film 60 to form a coating film 51, and the coating film 51 is dried to form a positive electrode composite material sheet 52, and the sheet is compressed to thereby manufacture. Then, as shown in FIG. Figure 6 As shown in (d), the positive electrode composite material sheet 53 is attached to the positive electrode core material 30, thereby obtaining a positive electrode 11 having a positive electrode composite material layer 31 formed by the positive electrode composite material sheet 53 on the surface of the positive electrode core material 30. It should be noted that the compression of the positive electrode composite material sheet 52 and the hot pressing of the stack of the positive electrode core material 30 and the positive electrode composite material sheet 53 can be performed at the same time as Figure 4 The manufacturing method shown was carried out under the same conditions.
[0078] In this process using the positive electrode composite material slurry 50, a drying process for volatilizing and removing the solvent is necessary, which causes the migration of the binder. Therefore, in the thickness direction of the positive electrode composite material sheet 52, the amount of the binder increases as it is farther away from the release film 60. In addition, in this process, Figure 6 As shown in (c), the positive electrode composite material sheet 52 is compressed in a state of a stacked body arranged on the release film 60. That is, the positive electrode composite material sheet 52 is compressed in a state constrained by the release film 60, and therefore, a distribution of pores is formed in the positive electrode composite material sheet 52, with more pores being formed closer to the release film 60.
[0079] Figure 6In the example shown, after the positive electrode composite material sheet 53 is peeled off from the release film 60, the positive electrode composite material sheet 53 is placed on the positive electrode core material 30 and hot pressed with the surface of the positive electrode composite material sheet 53 opposite to the release film 60 facing the positive electrode core material 30. Figure 6 In the positive electrode composite material layer 31 of the positive electrode 11 manufactured by the process shown in the figure, a pore distribution is formed in which the porosity of the first region 31a (a) < the porosity of the second region 31b (b) < the porosity of the third region 31c (c). In addition, a binder distribution is formed in which the content of the binder in the first region 31a (a) > the content of the binder in the second region 31b (b) > the content of the binder in the third region 31c (c).
[0080] like Figure 7 As shown in (c), after the positive electrode composite material sheet 52 is peeled off from the release film 60, the positive electrode composite material sheet 52 is compressed to produce a positive electrode composite material sheet 53. In this case, the positive electrode composite material sheet 52 is compressed in a state not constrained by the release film 60, so that a pore distribution is formed in the positive electrode composite material sheet 53 in which the porosity (a) of the first region 31a ≒ the porosity (c) of the third region 31c < the porosity (b) of the second region 31b. It should be noted that in this case, migration of the binding material also occurs due to the drying process.
[0081] like Figure 7 As shown in (d), the positive electrode composite material sheet 53 can be arranged on the positive electrode core material 30 with the surface of the positive electrode composite material sheet 53 on the release film 60 side facing the positive electrode core material 30 side, and hot pressing can be performed. Alternatively, the positive electrode composite material sheet 53 can be arranged on the positive electrode core material 30 with the surface of the positive electrode composite material sheet 53 on the opposite side of the release film 60 facing the positive electrode core material 30 side, and hot pressing can be performed. In the former case, a binder distribution is formed in the positive electrode composite material layer 31, in which the content of the binder in the first region 31a (a) < the content of the binder in the second region 31b (b) < the content of the binder in the third region 31c (c). On the other hand, in the latter case, a binder distribution is formed in which the content (a) > the content (b) > the content (c).
[0082] Figure 8 It is a diagram showing another example of the method for producing the positive electrode 11 . Figure 8 The process shown in the figure is different from the dry process of manufacturing a positive electrode composite material sheet from a powdered positive electrode composite material 40 in that a release film 60 is used. Figure 4 The process shown. Figure 8In the example shown, the release film 60 is supplied between the rollers 101b and 101c, and is stacked with the positive electrode composite material sheet 42, and the positive electrode composite material sheet 42 is compressed by a pair of rollers 102 in a state where the positive electrode composite material sheet 42 is arranged on the release film 60. In this case, a positive electrode composite material sheet 43x having a pore distribution in which the pores increase as they are closer to the release film 60 is produced.
[0083] Figure 8 In the example shown, the positive electrode composite material sheet 43x is placed on the positive electrode core material 30 and hot pressed with the surface of the positive electrode composite material sheet 43x opposite to the release film 60 facing the positive electrode core material 30. In this case, a pore distribution is formed in the positive electrode composite material layer 31 such that the porosity (a) of the first region 31a is less than the porosity (b) of the second region 31b is less than the porosity (c) of the third region 31c.
[0084] It should be noted that Figure 8 In the example shown, the release film 60 is peeled off after the positive electrode composite material sheet 42 is compressed and before the positive electrode composite material sheet 43x is hot-pressed, but the release film 60 may be peeled off after the hot-pressing. Figure 6 In the steps shown, the release film 60 may be peeled off after the heat pressing.
[0085] Description of Reference Numerals
[0086] 10 Secondary batteries
[0087] 11 Positive electrode
[0088] 12 Negative electrode
[0089] 13 Divider
[0090] 14 Electrode body
[0091] 16 Shell tank
[0092] 17 Sealing body
[0093] 18, 19 Insulation board
[0094] 20 Positive lead
[0095] 21 Negative lead
[0096] 22 Groove
[0097] 23 Internal terminal block
[0098] 24 Lower valve body
[0099] 25 Insulation components
[0100] 26 Upper valve body
[0101] 27 Cover
[0102] 28 Gasket
[0103] 30 Positive electrode core material
[0104] 31. Positive electrode composite material layer
[0105] 31a Area 1
[0106] 31b Area 2
[0107] 31c Area 3
[0108] 40 Positive electrode composite material
[0109] 41, 42, 43, 43x positive electrode composite sheet
[0110] 50 Positive electrode composite material slurry
[0111] 51 Coating
[0112] 52, 53 Positive electrode composite material sheet
[0113] 60 Release film
[0114] 100, 101a, 101b, 101c, 102, 103 Rollers
Claims
1. A battery electrode comprising: a core material; and a composite material layer, comprising an active substance and a binding material, and arranged on the surface of the core material, When the composite material layer is divided into three equal parts along the thickness direction and defined as a first region, a second region, and a third region in order from the core material side, the porosity of the second region is higher than the porosity of the first region, The difference (ac) between the porosity (a) of the first region and the porosity (c) of the third region is within the range of ±1%.
2. A battery electrode comprising: a core material; and a composite material layer, comprising an active substance and a binding material, and arranged on the surface of the core material, When the composite material layer is divided into three equal parts along the thickness direction and defined as a first region, a second region, and a third region in order from the core material side, the porosity of the second region is higher than the porosity of the first region, in, The porosity (b) of the second region is higher than the porosity (c) of the third region.
3. The battery electrode according to claim 1 or 2, wherein A difference (ba) between the porosity (b) of the second region and the porosity (a) of the first region is 0.5% or more and 10% or less.
4. The battery electrode according to claim 1 or 2, A difference (bc) between the porosity (b) of the second region and the porosity (c) of the third region is 0.5% or more and 10% or less.
5. The battery electrode according to claim 1, wherein The porosity (c) of the third region is higher than the porosity (b) of the second region.
6. The battery electrode according to claim 1 or 2, wherein A ratio of a difference between the content (a) of the binder in the first region and the content (c) of the binder in the third region relative to the content (a+b+c) is within a range of ±5%.
7. The battery electrode according to claim 1 or 2, wherein A ratio of a difference between the content (a) of the binder in the first region and the content (b) of the binder in the second region relative to the content (a+b+c) is within a range of ±5%.
8. The battery electrode according to claim 1 or 2, wherein The ratio of the difference between the content (b) of the binder in the second region and the content (c) of the binder in the third region relative to the content (a+b+c) is within the range of ±5%.
9. The battery electrode according to claim 1 or 2, wherein The content of the binder in the composite material layer increases in the order of the third region, the second region, and the first region.
10. The battery electrode according to claim 1 or 2, wherein The overall porosity of the composite material layer is 40% or less. 11 . A battery comprising: the battery electrode according to claim 1 ; and an electrolyte solution.
Citation Information
Patent Citations
Positive electrode plate for nonaqueous electrolyte secondary batteries
JP2005056743A
Method for manufacturing electrode for electrochemical element
JP2013077560A
Method for manufacturing electrode for lithium secondary battery, and granulated material
JP2015138658A
Positive electrode plate for nonaqueous secondary battery and nonaqueous secondary battery using the same
JP2012033372A